2015
DOI: 10.1017/jfm.2015.455
|View full text |Cite
|
Sign up to set email alerts
|

Plane shock waves and Haff’s law in a granular gas

Abstract: The Riemann problem of planar shock waves is analysed for a dilute granular gas by solving Euler-and Navier-Stokes-order equations numerically. The density and temperature profiles are found to be asymmetric, with the maxima of both density and temperature occurring within the shock layer. The density peak increases with increasing Mach number and inelasticity, and is found to propagate at a steady speed at late times. The granular temperature at the upstream end of the shock decays according to Haff's law (θ(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…The upstream Mach number can thus be a misleading metric to characterize the "granular" shock since the obstacle would see a different (and in-fact larger) Mach number upstream from the point of collision with granular particles. A similar conclusion has recently been noted in the case of plane granular shock waves [5]. The non-dimensional detachment length, δ/D, (see Fig.…”
Section: Detachment Region and The Sonic Linesupporting
confidence: 86%
See 2 more Smart Citations
“…The upstream Mach number can thus be a misleading metric to characterize the "granular" shock since the obstacle would see a different (and in-fact larger) Mach number upstream from the point of collision with granular particles. A similar conclusion has recently been noted in the case of plane granular shock waves [5]. The non-dimensional detachment length, δ/D, (see Fig.…”
Section: Detachment Region and The Sonic Linesupporting
confidence: 86%
“…Granular flows around an object have been the focus of numerous analytical [1][2][3], experimental [1,2] and simulation studies [1,4].The formation of plane shock waves [5], when a granular medium is perturbed faster than the velocity of sound, has been reported by previous studies. Experimental studies [6,7] have shown that a stagnant zone formation, similar to the classical "bow-shock" detachment (see Fig.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Namely, mass, momentum and energy conservation laws that govern the motion of a fluid. The classical Navier-Stokes equations in an Eulerian reference frame are given as [16,19]: mass balance/continuity equation where ρ is the mass-density of the fluid, U is the flow mass velocity, p is the hydrostatic pressure and e in is the specific internal energy of the fluid. Further, NS P ( ) and q NS ( ) represent the shear stress tensor and the heat flux vector, respectively, and I is the identity matrix.…”
Section: Classical Navier-stokes Equationsmentioning
confidence: 99%
“…A late suggestion to substitute the Navier-Stokes is given by Svärd [18].Generally, there are a number of experimental data that standard Navier-Stokes fail to predict. Shock wave structure predictions are a ubiquitous example of Navier-Stokes failure [4,6,19,20]. Experimental data of water flows in carbon nanotubes or confined pores is another research topic showing large deviations from the classical Hagen-Poiseuille equation [21,22].…”
mentioning
confidence: 99%